Metronomic chemotherapy for primary non-metastatic breast cancer: a systematic review of the literature = Metronomische Chemotherapie bei primärem nicht metastasierenden Brustkrebs : eine systematische Literaturübersicht - Banys-Paluchowski, Maggie; Schütz, Florian (Geburtshilfe und Frauenheilkunde, 2017)
Conventional chemotherapy is based on the "maximum tolerated dose" principle and aims at administering high doses of cytotoxic drugs followed by a rest period necessary for the body to recover. In the last decades alternative strategies have been developed to avoid serious side effects of conventional treatment, among them the metronomic chemotherapy. Much like a metronome keeps steady rhythm, metronomic therapy is administered continuously in low doses for a long time. In metastatic breast cancer, metronomic therapy is a valid option in pretreated or vulnerable patients and its use has recently been incorporated into various guidelines. In early breast cancer, the role of metronomic treatment remains to be clarified. A systematic review of PubMed/MEDLINE, ClinicalTrials.gov, the European Clinical Trials Database (EudraCT) and the Cochrane Database was conducted. In the present review, we discuss the current evidence on metronomic chemotherapy in non-metastatic breast cancer.